DEVELOPMENT OF ENDURANCE ABILITY OF 6TH CLASS PUPILS THROUGH TRACK AND FIELD EXERCISES AS AN AFTER-SCHOOL ACTIVITY - Dilmurod, Khasanov (Educational Research in Universal Sciences, 2023)
If we pay close attention to the lifestyle of middle schoolers, they are leading a hectic lifestyle, studying, doing housework, watching TV, playing computer and other things as most of them live a passive lifestyle. It is of paramount importance for them to find the right place in the future, to achieve effective results at work and, most importantly, to engage in physical education to improve their health. In this case, the development of endurance allows them to perform actions for a long time and increases the level of resistance of the body to fatigue. Endurance ability is one of the foundations of the structure of comprehensive physical training that reflects labour activity and functional capabilities. Physical education remains a very important factor in shaping a healthy lifestyle in the fast-paced world. People have a great need for movement, and it is important to develop their physical qualities. Endurance has a special place among physical abilities. At the same time, it is very important to study the stages of forming resilience in young people.